Know your men and women farmers: Ensuring host farmers in participatory trials represent heterogeneity within the target environment - Cairns, Jill E.; Zaman-Allah, Mainassara; Baudron, Frédéric; Voss, Rachel C.; Hassall, Kirsty L.; Euler, Michael A.; Amondo, Emily I.; Marenya, Paswel P.; Prasanna, Boddupalli M. (Wiley, 2025)
Societal Impact Statement: Gender responsive and more socially inclusive breeding strategies are needed to ensure new crop varieties, which offer greater yields in an increasingly variable climate, meet the needs of a diverse range of smallholder farmers. Participatory varietal selection actively involves farmers in testing and selecting new varieties at the end of the breeding process. We evaluated the inclusivity of a participatory maize breeding program in Zimbabwe. Our analysis found that setting targets for women farmer participation ensured adequate representation, but participatory research should move beyond simple targets and ensure the inclusion of different types of women and men farmers. Summary: There is growing interest in participatory varietal selection and gender-responsive breeding in research and development initiatives. On-farm testing is increasingly used to ensure that new varieties perform within the target environments. However, there are few established approaches for selecting host women and men farmers who reflect the diversity of the overall target population of smallholder farmers. This study sought to evaluate ex-post if recruited farmers within a participatory breeding network in Zimbabwe were representative of the surveyed population and pilot an approach to developing comprehensive farm typologies to ensure more gender-responsive and socially inclusive breeding. A sample of over 2,000 randomly selected women and men farmers, including those hosting breeding trials, were surveyed. A typology was constructed to group farms with similar characteristics associated with household demographics, maize production and resource endowments. This facilitated the subsample of trial-hosting farmers characteristics to be compared with the broader typology.The distribution of farm types selected by extension agents to host trials closely reflected the distribution of farm types within the surveyed population. Two farm types associated with women household heads and three types associated with men-headed households were identified, highlighting the heterogeneity within these groups. Other important factors of differentiation included farm assets, livestock ownership and maize production features. Sampling strategies that explicitly incorporate agronomic and socio-economic diversity within the target population should be used in the selection of host women and men farmers for participatory research to ensure appropriate gender and social inclusion.